Temporal patterns of sleep and eating among children during school closure in Japan due to COVID-19 pandemic: associations with lifestyle behaviours and dietary intake - Minami Sugimoto; Kentaro Murakami; Satoshi Sasaki (Cambridge University Press, 2023)
Abstract Objective: To identify temporal patterns of sleep and eating among school-age children during school closure due to the COVID-19 pandemic and to examine their associations with lifestyle behaviours and dietary intake. Design: In this cross-sectional study, questionnaires were used to assess sleep and eating times, lifestyle behaviours and dietary intake during school closure. Latent class analysis was performed to identify temporal patterns of sleep and eating based on self-reported clock times for wake-up, going to bed and eating meals. Lifestyle behaviours and dietary intake were compared between latent classes. Setting: Forty-eight primary and secondary schools in Japan. Participants: Totally, 6220 children (aged 8-15 years). Results: Four patterns, labelled 'Very early (20 % of children)', 'Early (24 %)', 'Late (30 %)' and 'Very late (26 %),' were identified and ordered according to the circadian timing. Latter patterns were characterised by later timings of sleep and eating, especially in clock times for wake-up, breakfast and lunch compared with earlier patterns. Children with latter patterns had a less physically active lifestyle, longer screen time (≥4 h/d), shorter study time (<2 h/d) and more frequent skipping of breakfast and lunch than those with earlier patterns. In addition, children with latter patterns had lower intakes of several vitamins, vegetables, fruits, fish and shellfish and dairy products and higher intakes of sugar and confectionaries and sweetened beverages. Conclusion: More than half of the participants had later wake-up, breakfast and lunch during school closure, which was associated with more unfavourable lifestyles and dietary intakes.